EMMA WOODHOUSE AS AN UNCONVENTIONAL HEROINE: A FEMINIST INTERPRETATION OF EMMA - Abdullayeva Zarinabonu Obid qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article deals with the heroes of the novel “Emma”, one of the most  popular  works  of  English  Romanticism  literature.  There  is  a  comprehensive analysis of female image.  A special place in the work of Jane Austen is occupied by the  novel  o”Emma”,  a  novel  that  presents  a  complex  and  independent  female protagonist whose personal growth challenges traditional expectations of womanhood. the article explores issues of female agency, economic independence, self-realization, and gender norms. Particular attention is paid to the ways in which Emma negotiates social conventions while maintaining a strong sense of individuality and autonomy. The analysis demonstrates that Austen's portrayal of Emma Woodhouse anticipates later feminist concerns by  emphasizing intellectual development, moral responsibility, and the right of women to shape their own identities. The findings suggest that Emma can be interpreted as an unconventional heroine whose experiences reflect both the limitations imposed upon women and the possibilities for female empowerment within a patriarchal society.